Pracoholizm jako przyczyna niezdolności do zawarcia małżeństwa - Mierzejewski, Krzysztof (Ius Matrimoniale, 2011)
This article shows that addiction to work (workaholism) can be a potential cause of person’s inability to contract marriage in the light of canon law. Workahlism is one of contemporary addictions, in which an individual gets addicted to certain actions and not substances. Nevertheless, addiction in consideration causes particular effects, also mental, and it strongly influences person’s functioning. It mainly causes damages to interpersonal bonds, personal life disruptions, health deterioration, reduction of happiness and even the loss of life. This paper describes the phenomenon of workaholism (a concept, diagnostic criteria, stages of development, causes and consequences of addiction to work). Next it presents how workaholism affects ability to take upon significant marriage duties. Presented analysis is based on Canon 1095 of The Code of Canon Law. This article might be of use for Church courts employees, in terms of interpretation of The Code of Canon Law: Canon 1095 in the context of addictions. It may also have scientific application.